Engajamento de crianças com Transtorno do Espectro Autista nas rotinas da educação infantil - Morais, Giovana Cássia de (Universidade Federal de São Carlos, 2022)
Child development monitoring is increasingly essential for identifying potential and difficulties in learning. Engagement in routines is one of the factors that can contribute to the achievement of children's goals in a variety of areas, whether they have typical or atypical development. The beginning of the school life of children with Autism Spectrum Disorder (ASD) can be a challenge for quality participation in Early Childhood Education routines. In this way, understanding the functioning and profile of engagement in school routines can make an important contribution, both to the educators and family members, and also to the gain of academic knowledge. Therefore, the present study aimed to identify how the engagement of children aged 3 to 5 years old with a diagnosis of ASD in the routines of Early Childhood Education occurred, from the point of view of educators. The research was carried out in the national territory and the method was quantitative and descriptive, without manipulation of variables. Data collection and analysis took place under the following structure: response to an online form via “Google Forms” by each child's educator, with questions of the ClaMEISR’s instrument - Classroom Measure of Engagement, Independence, and Social Relationships. The objective of the protocol is to help the school team and the family in the evaluation of the routines of children aged between 3 and 5 years old. The score was obtained through questions about activities carried out by the children during a day at school, making it possible to assess how engaged the child was in each of their routines, so this could be monitored and worked on. As a result, it was found that the children with ASD did not show sophisticated engagement in the analyzed routines, demonstrating the need for curricular adaptations as something fundamental for expanding engagement in the educational context for students who are part of school inclusion programs. In the conclusion there is the suggestion of future studies to cover different age groups, in order to understand the impacts of engagement in the scholar context, and also how the environmental factors may favor or limit it.
Participación de los niños con Trastorno del Espectro Autista en las rutinas de la primera infancia
Engagement of children with Autism Spectrum Disorder in early childhood routines
Keywords: Engajamento; Crianças; Terapia Ocupacional; Educação infantil; Transtorno do Espectro Autista; Engagement; Children; Occupational Therapy; Child Education; Autism Spectrum Disorder; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL